New Record of Different Yeast Isolates from Patients with Ear Infections Using DNA Sequencing in Al-Najaf Governorate, Iraq - Mohammad Mohsien Alrufae; Zuhair Hameed Abboud; Ban Mousa Hassan (Medical Journal of Babylon)
Background: Candida albicans may cause other chronic fungal infections in the human ear. Otomycosis is a common disease found in the general clinical setting of otolaryngology. Objectives: The present study aims to establish a database of fungal species causing ear canal, infections, characterize their genetics, and compare them with standard isolates documented in the National Center for Biotechnology Information global sites. Materials and Methods: A total of 120 samples were collected from patients with ear infections at Al-Sadder Medical City in Al-Najaf Province, and incubated at 37°C for 1–2 days for visible. A specific fungal genomic deoxyribonucleic acid (DNA) kit was used for the purification of young Candida colonies' DNA. Amplification of genes was carried out according to the experimental protocol, and the polymerase chain reaction products of Candida spp were sent to Macrogen Lab, USA, for sequencing. Results: The present study included a collection of 120 ear swab samples from patients with different ear infections, 47 (39.2%) samples of otitis externa, 71 (59.2%) samples of otitis media, and 2 (1.6%) from otitis enterna. C. albicans and Candida tropicals recorded the highest frequency. All 33 isolates were characterized as genotypes using two pairs of primers (ITS5-ITS4 and ITS3-ITS4), only 13/33 (39.5%) were classified as C. albicans, 8/33 (24.25%) were classified as C. tropicalis. DNA sequencing for five isolates was received online and aligned to the NCBI database using Blast software. Strain no. 3 was found to be the nearest neighbor to Meyerozyma guilliermondii strain MK267616.1 with an identity of 93.42%. Conclusion: The DNA sequencing method is considered one of the best methods for the diagnosis of mold and yeasts.